The causes of serous macular detachment excluding central serous chorioretinopathy - Turgut, Burak; Gul, Fatih Cem; Demir, Tamer; Celiker, Ulku (Dove Medical Press Ltd, 2010)
Objective: In our study, we investigate the causes of serous macular detachment (SMD) excluding central serous chorioretinopathy (CSC). Study design/patients and methods: A retrospective observational study. The medical records of 58 patients with SMD documented by optical coherence tomography (OCT) were reviewed retrospectively. The patients with CSC were excluded from the study. Ocular diseases accompanied with SMD, unilaterality or bilaterality, and demographical properties of the patients were evaluated. Results: Of the 58 patients with SMD in this study, 20 (34.4%) were women and 38 (65.5%) were men. The ages of patients were between 17 to 81 years (median 61.01 years). The causes of SMD were as follow: diabetic macular edema (DME) in 37 patients (63.8%), age-related macular degeneration (AMD) associated with choroidal neovascularization in 10 patients (17.24%), branch retinal vein occlusion in five patients (8.62%), central retinal vein occlusion in four patients (6.90%), Harada disease in one patient (1.72%) and Coat's disease in one patient (1.72%). Eighteen patients with DME, two patients had AMD associated with choroidal neovascularization, and one patient with Harada disease had bilateral SMD. The most common cause of SMD in both eyes was DME. Conclusions: The most common cause of SMD excluding CSC seems to be DME. The presence of SMD in retinal vascular diseases such as diabetes might affect the results of the treatment and the prognosis.
Keywords: serous macular detachment; causes; diabetic macular edema; age-related macular degeneration; excluding central serous chorioretinopathy